Una experiencia de investigación formativa en la formación inicial del profesorado: Actitudes hacia la vejez como tema de estúdio (Innovaciones Educativas, 2026)
This article presents an innovative didactic experience regarding a formative research process carried out within a human development course in initial teacher education. The didactic proposal had two objectives: the first consisted of providing a learning experience in research on a human development topic, and the second objective intrinsic to the inquiry proposal referred to generating an identification process of the perceptions and stereotypes among different age groups toward older adulthood, including the course students themselves, as a strategy for addressing one of the course thematic units. In the university classroom context, this work proposal aims to impact student awareness regarding their own stereotypes toward old age, promoting a more empathetic understanding of this population for planning educational actions in formal and non-formal contexts. The methodology was based on a descriptive study. For data collection, the CENVE questionnaire by Blanca et al. (2005) was used, which enabled a statistical analysis of the information obtained. Simultaneously, the reflection on attitudes and stereotypes toward older adults was enriched through a variant of the qualitative technique known as photovoice. The results show high reliability of the instrument and a tendency toward negative perceptions of older adulthood. The conclusions highlight the relevance of educational processes as key tools for transforming these attitudes and contributing to the improvement of this population's quality of life. In this context, formative research emerges as a valuable pedagogical practice, strengthening students’ research skills and fostering a critical perspective on social reality.
Keywords: higher education; teacher education; inclusive education; research; aging